2015
DOI: 10.1097/dcr.0000000000000413
|View full text |Cite
|
Sign up to set email alerts
|

Mesocolic Lymph Node Number, Size, and Density

Abstract: In this descriptive anatomical study, the median number of lymph nodes in the sigmoid and ascending mesocolon was 71 and 61. Ascending mesocolic nodes were significantly larger than sigmoid mesocolic nodes. These anatomical findings are relevant to the interpretation of lymph node yields after the surgical resection of colon cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The average number of LNs in our results was 62.0 ± 22.3, similar to Ahmadi et al’s 24 study, which revealed 61 and 71 median LNs per cadaver in the ascending mesocolon and sigmoid, respectively. The research of Hida et al 25 showed that the mean number of nodes examined per patient was 76.4 after the clearing method was performed.…”
Section: Discussionsupporting
confidence: 91%
“…The average number of LNs in our results was 62.0 ± 22.3, similar to Ahmadi et al’s 24 study, which revealed 61 and 71 median LNs per cadaver in the ascending mesocolon and sigmoid, respectively. The research of Hida et al 25 showed that the mean number of nodes examined per patient was 76.4 after the clearing method was performed.…”
Section: Discussionsupporting
confidence: 91%
“…According to existing research, age, tumor location, tumor size and T stage had been shown to affect LNM in colorectal cancer 17,29,30 Cancer risk communication in sensitivity and speci city for preoperative N stage remains di cult when compared to T stage because differentiating between malignant and reactive lymph node enlargement is di cult 34 . Therefore, studies have aimed at improving the detection rate for positive lymph nodes [35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…Although more emphasis should be placed on lymph nodes yield, fatty replacement is one of the major obstacles. This di culty lied in the recognition of LNs in adipose tissue, and it had been reported that fatty in ltration was occurred in about 30% of LNs detected from specimen [4,34]. Another obstacle is that more than 90% of LNs in mesocolons were smaller than 5mm and almost 60% were less than 2mm in maximum length [4].…”
Section: Discussionmentioning
confidence: 99%
“…This di culty lied in the recognition of LNs in adipose tissue, and it had been reported that fatty in ltration was occurred in about 30% of LNs detected from specimen [4,34]. Another obstacle is that more than 90% of LNs in mesocolons were smaller than 5mm and almost 60% were less than 2mm in maximum length [4]. Furthermore, RCC has been considered to have higher lymph nodes yield because of the longer colon needed to be respected, a greater proportion of tumors with microsatellite instability, and better antitumor immune response [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation